The - Christian, James L.
Oriented toward historical philosophy or introductory philosophy courses, this text seeks to acquaint students with the history of western critical thinking in an accessible and appealing format. The WISDOM SEEKERS gathers together a multitude of insights into man's eternal attempts to make sense of the human story. Coverage ranges from the beginnings of philosophical thought, the pre-Socratic philosophers, the Golden Age of Athens, the eclipse of philosophy throughout the Dark Ages, its resurrection during the Renaissance, the emergence of empirical philosophy during the last four centuries, and the career of philosophy during the twentieth century and its eclipse by the sciences